Differences in the efficacy of S‐1 monotherapy according to histological type in pretreated patients with advanced non‐small cell lung cancer. Issue 2 (March 2014) - Hisamatsu, Yasushi; Murakami, Haruyasu; Akamatsu, Hiroaki; Kimura, Madoka; Mori, Keita; Imai, Hisao; Ono, Akira; Shukuya, Takehito; Taira, Tetsuhiko; Kenmotsu, Hirotsugu; Naito, Tateaki; Endo, Masahiro; et al.
Abstract Background S‐1 is a novel antimetabolic agent that inhibits thymidylate synthase. The expression of thymidylate synthase is higher in squamous (Sq) non‐small cell lung cancer (NSCLC) than in non‐Sq NSCLC. The aim of this retrospective study was to assess the efficacy of S‐1 monotherapy for advanced NSCLC according to the histological subtype. Methods We reviewed the clinical records of patients with advanced NSCLC treated with S‐1 monotherapy as second‐ or third‐line therapy between May 2005 and July 2012 at the Shizuoka Cancer Center. Results A total of 71 patients were included in this retrospective study. Patient characteristics were similar in the Sq NSCLC (n = 15) and non‐Sq NSCLC (n = 56) groups, except with regard to gender and smoking status. The overall response rates were 0% (95% confidence interval [CI] 0–17%) for Sq NSCLC and 11% (95% CI 3–19%) for non‐Sq NSCLC (P = 0.33). For Sq NSCLC and non‐Sq NSCLC, the median progression‐free survival times were 2.1 and 2.8 months (P = 0.02), respectively, and the median overall survival times were 6.1 and 10.1 months (P = 0.01), respectively. Conclusion S‐1 monotherapy may be more effective in patients with non‐Sq NSCLC than in those with Sq NSCLC.